Do fiscal transfers foster regional economic growth? - Naftaly Mose (Financial Internet Quarterly, 2021)
Fiscal transfer development across the world today has been in part driven by assertions of a supposed 'economic dividend' linked with the devolved financial spending. There is, however, little empirical evidence to validate these assertions in Kenya. It is against this background that this study was carried out to estimate the end product of fiscal transfer on regional economic growth in Kenya using a secondary panel data set. Using the ARDL estimation technique the long -run and error correction estimates of the model were generated. The findings revealed that increased fiscal transfer in recurrent budgets accelerates regional growth, hence confirming the Keynesian hypothesis. Conversely, fiscal transfer in capital expenditure was insignificant. This study recommends the need for policymakers to put in place policies and strategies that will improve budget allocation and execution in capital budgets so as to improve physical infrastructure and thus boost private productivity and consequently regional income growth.
Keywords: E62; O23; H54; G51; 330; Regional Economic Growth; Fiscal Transfers; Capital; Recurrent; Kenya